Epistemologi Tafsir Ilmi dalam Tafsir al-Muntakhab - Nurhayati Nurhayati (Lembaga Yasin AlSys, 2026)
Although tafsir ilmi (scientific exegesis) and the integration of revelation and science have been addressed in a number of previous studies, research that specifically examines the epistemological structure and methodological consistency of Tafsir Al-Muntakhab, particularly in the interpretation of cosmological verses (āyāt kauniyyah), remains limited. This study aimed to analyse the epistemology of tafsir ilmi in Tafsir Al-Muntakhab by highlighting the patterns of reasoning, the structure of knowledge, and the hermeneutical principles used in relating modern scientific findings to the meanings of the verses. The study employed a qualitative approach with a library research design, in which data were collected through the identification and close reading of the text of Tafsir Al-Muntakhab alongside relevant literature on tafsir methodology and Islamic epistemology, and were then analysed using content analysis and critical reading to identify patterns of argumentation, the use of scientific sources, and the limits of interpretation. The findings show that Tafsir Al-Muntakhab develops a relatively moderate model of revelation–science integration by positioning scientific knowledge as a pedagogical instrument to elucidate the meanings of verses and broaden readers’ horizons of understanding. However, the epistemological analysis also reveals methodological inconsistencies in several sections, particularly when interpretation relies on scientific theories that are tentative or not yet well established, thereby increasing the risk of eisegesis and confirmation bias. These findings contribute to strengthening the discourse on contemporary tafsir methodology by underscoring the need for a more rigorous epistemological framework, including criteria for selecting scientific findings, principles of verification, and clear boundaries between the core meaning of verses and the illustrative-explanatory function of science. The study concludes by emphasising the importance of clearly defined methodological limits so that the integration of revelation and science in tafsir ilmi can be justified scientifically, while also opening avenues for further research on formulating evaluative standards for tafsir ilmi in modern exegetical works.